Scratch-free abrasive composites and abrasive cleaning articles
By using a structured abrasive product, the product consists of a formal abrasive complex on the bottom surface of the concave polygon, which solves the problem of high -value surfaces and difficulty removal of existing cleaning products, and achieves efficient and durable cleaning effects.
Patent Information
- Application Number
- CN202380046777.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-24
AI Technical Summary
Existing cleaning products are prone to damage high-value surfaces during use and are difficult to effectively remove dirt without leaving any traces.
Employing structured abrasive articles consisting of a shaped abrasive composite with a concave polygonal bottom surface, formed by dispersing a mineral phase or particulate phase in an organic binder phase, to provide high rinse performance and no damage to the substrate being cleaned Cause obvious damage.
Efficient dirt removal is achieved without damaging the surface, and the abrasive compound is durable and abrasive and rinses clean quickly.
Smart Images

Figure CN119365112A_ABST
Abstract
Description
Background Art
[0001] Consumer interest in non-scratch rinsing / cleaning products for household cleaning is increasing as consumers desire to protect high-value surfaces that are susceptible to damage if they come in contact with hard minerals and resins. Consumers are also interested in cleaning products that do not become dirty during the cleaning process. That is, people are interested in cleaning products that prevent dirt from accumulating on the surface of the cleaning product, but also rinse away the dirt after use.
[0002] Informal theories of abrasive performance posit that workpiece material removal rates are related to the mechanical properties (i.e., hardness) and size and shape (i.e., sharpness) of the abrasive material. On the other hand, the potential for an abrasive material to create a scratch in a workpiece is often discussed in terms of the relative hardness of the abrasive material and the workpiece. Although size and shape affect the geometry of the scratch created by the abrasive, the formation of a scratch requires that the abrasive material deform the workpiece. To do this, the abrasive material must be locally harder than the workpiece. Therefore, if the abrasive material is not hard enough to deform the workpiece, dirt located on the workpiece surface that is harder than the workpiece itself can be effectively removed by an abrasive material having a size and shape suitable for high dirt removal rates, i.e., relatively tall protrusions with relatively sharp edges. Summary of the invention
[0003] In one embodiment, the present invention is a structured abrasive article comprising a substrate having a first major surface and a second major surface, and a plurality of shaped abrasive composites. Each of the shaped abrasive composites comprises a bottom surface in contact with the first major surface of the substrate. Each of the bottom surfaces is in the shape of a concave polygon, and each of the concave polygons has a convex hull with n sides.
[0004] In another embodiment, the present invention is a structured abrasive article comprising a substrate having a first major surface and a second major surface, and at least one shaped abrasive composite having a bottom surface. The bottom surface of the at least one shaped abrasive composite is positioned on the first major surface of the substrate and has at least one reentrant angle.
[0005] In yet another embodiment, the present invention is a shaped abrasive composite comprising a binder phase and a microparticle phase dispersed within the binder phase.The shaped abrasive composite has at least one reentrant corner. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figures 1 to 11 Configurations of shaped abrasive composites according to various exemplary embodiments are shown. DETAILED DESCRIPTION
[0007] The present invention is an abrasive composite that is designed by geometry and composition to have high rinsing performance without causing significant damage to the underlying substrate being cleaned. In one embodiment, the abrasive composite can be used for household cleaning, which causes substantially no damage or minimal damage to materials such as, for example, poly(tetrafluoroethylene), stainless steel, and hard plastics. After use for cleaning, the abrasive composite can be substantially rinsed clean of debris removed from the surface being cleaned. In addition, the abrasive composite of the present invention is durable and has good abrasive properties.
[0008] The abrasive composite of the present invention is formed by dispersing a mineral phase or a microparticle phase in an organic binder phase. In the abrasive composite, the microparticles are bonded together by a binder, which serves as a dispersion medium for the microparticles and, if necessary, as a means of attaching the abrasive composite to a substrate or backing. The microparticles are mainly used as fillers and viscosity modifiers in uncured liquid binders. In contrast, the microparticles of conventional coated abrasives or nonwoven abrasives generally have high Mohs hardness values and can remove a large amount of material from the surface contacted by the microparticles by plowing or cutting mechanisms. The amount of material removed depends on the shape, hardness and size of the particles, as well as the pressure, speed and geometry of the grinding operation. In this application, the gouges formed on the surface by the removed material are framed as "scratches". Although individual microparticles with low Mohs hardness values (i.e., less than or equal to about 3) may not produce visible scratches on the test surface, according to the general mixing rules of the composite, the microparticles can affect the scratches by changing the mechanical properties of the composite. In one embodiment, the abrasive composite of the present invention contains microparticles with a Mohs hardness of less than or equal to about 3.
[0009] Although abrasive compositions with higher Mohs hardness or higher modulus generally result in higher cleaning performance, they also result in increased amounts of surface damage or scratching. Conversely, although abrasive compositions with lower modulus generally help avoid surface damage or scratching, they also reduce the cleaning performance of the abrasive composite. Similar correlations between scouring / scratching and the glass transition temperature (Tg) of the binder resin at a given temperature can also be empirically observed. By using a miscible blend of a soft binder component and a hard binder component, the modulus and glass transition temperature of the binder mixture can be adjusted to optimize the balance of cleaning performance and surface damage, avoiding the more expensive molecular engineering required to synthesize a single material with the desired glass transition temperature and modulus.
[0010] Examples of particulate particles having a Mohs hardness of less than about 3 include, but are not limited to, clays (such as kaolin, montmorillonite, illite, chlorite clay, talc, soapstone), gypsum, calcium carbonate (such as limestone and marble), mica, rock salt, and jet stone. In addition, many soft organic materials can provide the same functionality as soft particulate mineral particles, such as crushed or ground shells of nuts / fruits, including, but not limited to, almonds, argan, coconut, hazelnut, macadamia, pecan, pine, pistachio, and walnuts; crushed or ground kernels / grains of fruits, including, but not limited to, apricots, olives, peaches, cherries, plums, palms, and tagua; crushed or ground corn cobs; crushed or ground shells of arthropods; wood flour; crushed or ground synthetic polymeric materials, including, but not limited to, any thermoplastic polymer or any thermosetting polymer; and crushed, ground or unmodified naturally derived polymeric materials, including, but not limited to, polyhydroxyalkanoates; precisely shaped synthetic polymeric materials. In one embodiment, the abrasive composite comprises more than one type of particulate particles. In one embodiment, the abrasive composite includes between about 26% and about 80%, specifically between about 47% and about 75%, and more specifically between about 58% and about 72% by weight of microparticle particles.
[0011] The binder of the abrasive composite must be able to provide a medium in which the microparticles can be distributed. The binder generally includes a soft crosslinkable binder component, a hard crosslinkable binder component, and a material capable of initiating addition polymerization. When polymerized, the soft crosslinkable binder component has a glass transition temperature below room temperature (thus being rubbery and deformable) and a modulus of less than about 150 MPa. In one embodiment, the soft crosslinkable binder component includes urethane diacrylate or triacrylate. Examples of suitable soft crosslinkable binder components include, but are not limited to, aliphatic urethane diacrylates. In one embodiment, when polymerized, the soft crosslinkable binder component has an elongation at break greater than about 25%. The hard crosslinkable binder component has a glass transition temperature above room temperature (thus being glassy and rigid). In one embodiment, the hard crosslinkable binder component includes a difunctional or trifunctional acrylate. Examples of suitable hard crosslinkable binder components include, but are not limited to: trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, and pentaerythritol tetraacrylate.
[0012] In one embodiment, the binder is capable of curing or gelling relatively quickly so that the abrasive composites can be manufactured quickly. Some binders gel relatively quickly but take longer to fully cure. Gelation maintains the shape of the composite until curing begins. Fast curing or fast gelling binders can produce coated abrasive articles with abrasive composites of high consistency. Examples of binders suitable for use in the present invention include, but are not limited to, thermoplastic resins, phenolic resins, aminoplast resins, urethane resins, epoxy resins, acrylate resins, acrylated isocyanurate resins, urea-formaldehyde resins, isocyanurate resins, acrylated urethane resins, acrylated epoxy resins, hot melt adhesives, and mixtures thereof.
[0013] Depending on the binder used, curing or gelling can be performed by an energy source known to those skilled in the art. The energy source can include, but is not limited to, heat, infrared radiation, electron beam, ultraviolet radiation, or visible radiation. Radiation-curable binders are any binders that can be at least partially cured or at least partially polymerized by radiation energy. Typically, these binders polymerize by free radical mechanisms.
[0014] If the adhesive is cured by ultraviolet radiation, a photoinitiator is required to initiate free radical polymerization. Examples of photoinitiators include, but are not limited to, organic peroxides, azo compounds, quinones, benzophenones, nitroso compounds, acyl halides, hydrazones, mercapto compounds, pyrylium compounds, triacryloyl imidazoles, bisimidazoles, chloroalkyl triazines, benzil ketals, thioxanthones, and acetophenone derivatives. Other examples include, but are not limited to, benzoin ethers and derivatives thereof, such as α-methylbenzoin; α-phenylbenzoin; α-allylbenzoin; α-benzylbenzoin; benzoin ethers, such as benzil dimethyl ketal (commercially available as IRGACURE 651 from Ciba Specialty Chemicals, Tarrytown, NY), benzoin methyl ether, benzoin ethyl ether, benzoin n-butyl ether; acetophenone and derivatives thereof, such as 2-hydroxy-2-methyl-1-phenyl-1-propanone (e.g., available as DAROCUR 1173 from Ciba Specialty Chemicals) and 1-hydroxycyclohexyl phenyl ketone (e.g., available as IRGACURE 184 from Ciba Specialty Chemicals). Chemicals); 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone (e.g., available as IRGACURE 907 from Ciba Specialty Chemicals); 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl]-1-butanone (e.g., available as IRGACURE 369 from Ciba Specialty Chemicals). Other examples include phosphorus-containing organic molecules such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (e.g., available as IRGACURE 819 from Ciba Specialty Chemicals) and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate (e.g., available as TPO-L from Ciba Specialty Chemicals).Still more useful photoinitiators include, for example, pivaloin ethyl ether, anisole ethyl ether, anthraquinone (e.g., anthraquinone, 2-ethylanthraquinone, 1-chloroanthraquinone, 1,4-dimethylanthraquinone, 1-methoxyanthraquinone, or benzanthraquinone), halomethyl triazines, benzophenone and its derivatives, iodonium and sulfonium salts, titanium complexes such as bis(η5-2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium (e.g., available as CGI 784DC from Ciba Specialty Chemicals); and halogenated nitrobenzenes (e.g., 4-bromomethylnitrobenzene), mono- and bisacylphosphines (e.g., available as IRGACURE 1700, IRGACURE 1800, IRGACURE 1850, and DAROCURE 1860). 4265 is available from Ciba Specialty Chemicals.) In one embodiment, more than one photoinitiator is used.
[0015] One or more spectral sensitizers (e.g., dyes) may be used with the photoinitiator, for example, to increase the sensitivity of the photoinitiator to a particular source of actinic radiation. In one embodiment, the abrasive composite comprises between about 15% and about 35%, specifically between about 16% and about 28%, and more specifically between about 18% and about 26% by weight of a soft crosslinkable binder component. In one embodiment, the abrasive composite comprises between about 8% and about 28%, specifically between about 10% and about 15%, and more specifically between about 11% and about 14% by weight of a hard crosslinkable binder component. In one embodiment, the abrasive composite comprises between about 0.5% and about 5%, specifically between about 0.6% and about 1%, and more specifically between about 0.7% and about 0.9% by weight of a material capable of initiating addition polymerization.
[0016] The binder may be radiation curable via an addition polymerization mechanism. To facilitate bonding between the binder and the microparticles, a silane coupling agent may be included in the slurry of the microparticles and the binder precursor. In one embodiment, the silane coupling agent may be present in an amount of about 1% by weight, specifically between about 0.05% and about 0.4%, and more specifically between about 0.1% and about 0.3%. However, those skilled in the art will appreciate that other amounts may also be used, depending, for example, on the size of the mineral. Suitable silane coupling agents include, but are not limited to, methacryloxypropylsilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, 3,4-epoxycyclohexylmethyltrimethoxysilane, γ-glycidoxypropyl-trimethoxysilane, and γ-mercaptopropyltrimethoxysilane (e.g., available from Witco Corp. of Greenwich, Conn. under the trade names A-174, A-151, A-172, A-186, A-187, and A-189, respectively), allyltriethoxysilane, diallyldichlorosilane, divinyldiethoxysilane, and m-, p-phenylethyltrimethoxysilane (e.g., available from United Chemical Industries, Inc. of Bristol, Pa. under the trade names A0564, D4050, D6205, and S1588, respectively). Industries, Bristol, Pa.), dimethyldiethoxysilane, dihydroxydiphenylsilane, triethoxysilane, trimethoxysilane, triethoxysilanol, 3-(2-aminoethylamino)propyltrimethoxysilane, methyltrimethoxysilane, vinyltriacetoxysilane, methyltriethoxysilane, tetraethyl orthosilicate, tetramethyl orthosilicate, ethyltriethoxysilane, amyltriethoxysilane, ethyltrichlorosilane, amyltrichlorosilane, phenyltrichlorosilane, phenyltriethoxysilane, methyltrichlorosilane, methyldichlorosilane, dimethyldichlorosilane, dimethyldiethoxysilane, and mixtures thereof.
[0017] For special purposes, other materials may be added to the abrasive composite, including but not limited to: monofunctional acrylic monomers, thermal free radical initiators, promoters, polymer waxes or beads, leveling agents, wetting agents, matting agents, colorants, dyes, pigments, slip agents, adhesion promoters, fillers, rheology modifiers, thixotropic agents, plasticizers, UV absorbers, UV stabilizers, dispersants, antioxidants, antistatic agents, lubricants, sunscreens, defoamers, antimicrobial agents, fungicides, and combinations thereof. In one embodiment, the additives are organic. In one embodiment, the abrasive composite contains up to about 2% by weight, specifically between about 0.1% and about 1.8%, and more specifically between about 0.8% and about 1.4% dispersant. In one embodiment, the abrasive composite contains up to about 1% by weight, specifically between about 0.05% and about 0.4%, and more specifically between about 0.1% and about 0.3% coupling agent. In one embodiment, the abrasive composite comprises up to about 1%, specifically up to about 0.5%, and more specifically up to about 0.3% colorant by weight. In a specific embodiment, the abrasive composite comprises between about 0.5% and about 5%, specifically between about 0.6% and about 1%, and more specifically between about 0.8% photoinitiator by weight; between about 25% and about 55%, specifically between about 35% and about 45%, and more specifically between about 38% and about 42% first microparticle particles by weight; and between about 1% and about 30%, specifically between about 12% and about 25%, and more specifically between about 16% and about 24% second microparticle particles by weight. Although the abrasive composite includes a binder phase and a mineral phase, it is believed that the mineral phase does not directly contribute to the rinsing ability of the abrasive composite and acts more as a filler due to its relative softness and small size. Rather, the flushing properties result from the combined properties of the binder phase and the mineral phase as a whole.
[0018] In one embodiment, the abrasive composite of the present invention is used to form a structured abrasive article, which includes a plurality of substantially identical shaped abrasive composites attached to a substrate. As used herein, "shaped abrasive composites" refers to abrasive composites having an experimentally designed shape that has excellent flushing performance and durability. In one embodiment, the designed shape can be formed by curing one or more binder components of a flowable mixture that also contains soft mineral particles, while the mixture is supported on a backing and fills the cavity on the surface of the production tool. Such shaped abrasive composites have a shape substantially the same as the reverse side of the cavity. In one embodiment, the shaped abrasive composite may be conical, and its size is substantially the same across all composite features.
[0019] The shaped abrasive composites of the present invention include in-plane geometries with concave angles. Such shapes are also referred to herein as concave shapes or concave polygons. That is, the shaped abrasive article has at least one interior angle between 180° and 360°. The concave polygon has a convex hull with n sides. In one embodiment, n is at least 3. The washing performance of the abrasive composites of the present invention having concave interior angles is greater than the washing performance of comparative abrasive composites having only internal convex angles or interior angles less than 180°. Abrasive composites having only convex interior angles are also referred to herein as convex polygons. Figure 1 and Figure 2 Exemplary concave polygons and exemplary convex polygons are shown.
[0020] The abrasive composite of the present invention includes a bottom surface and one or more top surfaces. The bottom surface forms a concave polygonal shape of the abrasive composite and has 1 to n vertices, the vertices having concave internal angles. Increasing the number of vertices and edges of the abrasive composite can result in reduced flushing performance. Without being bound by theory, in general, as the number of edges increases, the bearing area of the pattern also increases, reducing the pressure on each individual edge and reducing its ability to cut soil. In one embodiment, the longest diagonal of the polygon of the bottom surface is between about 0.3 mm and about 6 mm.
[0021] The top surface of the abrasive composite can include a single face or multiple faces. The top surface can be defined as a point, a line, or a plane. In one embodiment, the top surface of the abrasive composite can be flat. Flattening the top surface can soften the tactile perception of the formed features.
[0022] In one embodiment, the bottom surface has a star-shaped polygonal shape, and in particular a regular star-shaped polygon. Figure 3 and Figure 4 A top view and a side view of a four-point star polygon are shown.
[0023] In one embodiment, a feature may have zero planes of symmetry. In one embodiment, one or more of the top surfaces may touch or intersect the bottom surface. Figure 5 An example of an embodiment is shown in , where the abrasive composite has zero planes of symmetry and has a top surface that intersects a bottom surface. As can be seen from this figure, the abrasive composite does not have to be a regular polygon.
[0024] Shaped abrasive composites and structured abrasive articles having shaped abrasive composites can be formed by a production tool. The production tool has a surface defining a major plane, which contains a plurality of cavities that expand from the major plane as indentations. These cavities define the reverse shape of the abrasive composite and are responsible for the shape, size and arrangement of the abrasive composite. The cavity can be provided in substantially any geometric shape opposite to the geometric shape suitable for the abrasive composite. For example, the abrasive composite can be a cube, a cylinder, a prism, a hemisphere, a rectangle, a cone, a truncated pyramid, a cone, a truncated cone or a column. The pattern in which the cavities are arranged is selected to balance the washing performance, the visual aesthetics, the tactile perception of the individual composite features and the consumption of the composite precursor.
[0025] The production tool may be in the form of a belt, a sheet, a continuous sheet or web, a coating roller (such as a rotogravure roller), a sleeve mounted on a coating roller, or a mold. In one embodiment, the production tool is replicated from a master tool. The master tool may be manufactured by any conventional technique known to those skilled in the art, including but not limited to photolithography, embossing, engraving, hobbing, electroforming, and diamond turning. U.S. Pat. No. 5,851,247 (Stoetzel et al.) describes a production tool made of a thermoplastic material that can be replicated from a master tool, and the U.S. Pat. No. is incorporated herein by reference. When the production tool is replicated from the master tool, the master tool is provided with the reverse side of the pattern desired for the production tool. In one embodiment, the master tool is made of nickel-plated metal, such as nickel-plated aluminum, nickel-plated copper, or nickel-plated bronze. The production tool can be replicated from the master tool by pressing a sheet of thermoplastic material onto the master tool while heating the master tool and / or the thermoplastic sheet so that the thermoplastic material is embossed with the master tool pattern. Alternatively, the thermoplastic material can be directly extruded or cast onto the master tool. The thermoplastic material is then cooled to a solid state and then separated from the master tool to produce a production tool. The production tool may also optionally include a release coating to allow the abrasive article to be more easily released. Examples of suitable release coatings include, but are not limited to, silicones and fluorochemicals. Preferred methods for producing production tools are disclosed in U.S. Pat. Nos. 5,435,816 (Spurgeon et al.), 5,658,184 (Hoopman et al.) and U.S. Pat. No. 08 / 923,862 ("Method and Apparatus for Knurling a Workpiece, Method of Molding an Article with Such Workpiece, and Such Molded Article" filed on September 3, 1997) (Hoopman), the disclosure of which is incorporated herein by reference.
[0026] In one embodiment, a structured abrasive article can be manufactured by first introducing a flowable and curable slurry containing a mixture of a binder precursor and a plurality of minerals into a cavity contained on the outer surface of a production tool to fill such a cavity. Then a substrate having a first major surface and an opposite second major surface is introduced into the filled cavity of the outer surface of the production tool so that the slurry wets one major surface of the substrate to form an intermediate product. Then the binder is cured to form a shaped composite coated abrasive product before the intermediate product leaves the outer surface of the production tool. Then the structured abrasive product is removed from the surface of the production tool. In another embodiment, the abrasive product can be prepared by first introducing a flowable and curable slurry containing a mixture of a binder precursor and a plurality of minerals into the front side of the substrate so that the slurry wets the front side of the substrate to form an intermediate product. Then the slurry is introduced into the receiving side of the intermediate product to the outer surface of the production tool, having a plurality of cavities in its outer surface so that the cavities are filled. Then the binder precursor is cured to form a shaped composite coated abrasive product before the intermediate product leaves the outer surface of the production tool. The abrasive article is then removed from the surface of the production tool.In both methods described, in one embodiment, the steps are performed in a continuous manner, thereby providing an efficient method for making the structured abrasive article of the present invention.
[0027] When forming a structured abrasive article, a plurality of shaped abrasive composites are attached to at least one major surface of a substrate. The shaped abrasive composites provide a three-dimensional shape that protrudes outward from the surface of the substrate. The abrasive composites can be arranged on the substrate in a pattern (i.e., a non-random array) or in a disordered or random array. In one embodiment, the abrasive composites are arranged on the substrate in a non-random array that exhibits a certain degree of repeatability.
[0028] The materials suitable for the substrate of the present invention include but are not limited to: polymer film, paper, cloth, metal film, vulcanized fiber, nonwoven substrate, their combination and their chemically treated form. In one embodiment, the substrate is a polymer film, such as polyester or polyurethane film. In one embodiment, the substrate is transparent to ultraviolet radiation. In one embodiment, the substrate is coated with an adhesion promoting layer, such as poly (ethylene-to-acrylic acid), or a UV curable "bonding coating", or undergoes adhesion promoting surface modification, such as corona or flame treatment or electron beam irradiation. After forming the abrasive article, the substrate can be laminated to another substrate. For example, the substrate can be laminated to a flexible or rigid polyurethane foam material, thereby providing the user with the means to effectively operate the abrasive.
[0029] Example
[0030] The present invention is described in more detail in the following examples which are intended to be used as illustrations only, since many modifications and variations within the scope of the present invention will be apparent to those skilled in the art. Unless otherwise indicated, all parts, percentages and ratios reported in the following examples are based on weight. Where applicable, brand names and trade names are shown in all capital letters.
[0031] Table 1: Materials List
[0032]
[0033]
[0034] The formulations of Examples 1-8 are listed in Table 2.
[0035] Table 2: List of formulations for structured abrasive article examples
[0036]
[0037]
[0038] Test Method
[0039] Schiefer cutting text
[0040] To evaluate the relative abrasiveness of the articles of the present invention, the articles to be tested were cut into circular samples having a diameter of approximately 4.5 cm. The articles were secured to the drive plate of a Schiefer abrasion tester (available from Frasier Precision Company of Gaithersburg, Maryland) using plastic bristle fasteners available from Minnesota Mining and Manufacturing Company under the trade name "INSTA-LOK". A circular acrylic workpiece (available from American Cyanamid Co. under the trade name "ACRYLITE") was used for each of the test articles. The workpieces were approximately 10.16 cm in diameter and approximately 0.317 cm thick. The initial dry weight of each workpiece was recorded, and the workpiece was secured to the lower turntable of the tester using double-sided foam tape. The test was conducted for 5000 revolutions under a load of 2.26 kg while applying water to the surface of the acrylic disk at a rate of 40 to 60 drops / minute. The final weight of the workpiece was then determined, and the weight loss of the acrylic disk during the test was given as the result (reported in grams / 5000 revolutions).
[0041] Food Soil Removal Test
[0042] In order to determine the initial effect of the rinse product on removing carbonized food soil from a stainless steel plate (10.16 cm diameter x 0.31 cm thick), the measured amount of the blended food soil composition was applied to the stainless steel plate and baked at 232°C for 30 minutes. The blended food soil composition includes about 120g tomato juice, about 120g cherry juice, about 120g ground beef (70% lean meat), about 60g cheddar cheese shreds, about 120g whole milk, about 20g white all-purpose flour, about 100g granulated sugar and 1 AA grade egg. The plate was alternately coated and baked three times, weighed, and then attached to the lower turntable of the Schiefer abrasion tester modified to adapt to the plate. A head weight of 2.26kg (5 pounds) was used as the applied force. The sample with a diameter of 4.5cm tested was saturated with water, centered and fastened against the upper turntable of the test machine, and tested 50 cycles under wet conditions by lubricating the plate with water at a speed of 1 drop / second. The dry weight of the disk (in milligrams) was determined after the desired number of revolutions and the weight loss of the dried disk was recorded.
[0043] Quality Factor
[0044] The figure of merit is used to compare rinse performance and substrate damage and is obtained by dividing the output of the Food Soil Removal Test (in mg / 50 cycles) by the output of the Schiefer Cut Test (in grams / 5000 cycles).
[0045] Comparison with other flushing products
[0046] The average food soil removal (based on the Food Soil Removal Test), average acrylic cut (based on the Schiefer Cut Test), and the ratio of food soil removal to acrylic cut (quality factor) for Examples 1 and 2 and Abrasive Laminates 1 and 2 are shown in Table 3 below, both with a 4-point star.
[0047] Table 3: Comparison of two formulations with a standard home care product for food soil removal and acrylic cutting.
[0048]
[0049] As can be seen from Table 3 above, the articles of Example 1 and Example 2 including the formed flushing feature greatly outperform conventional heavy duty The product showed greater selectivity in removing soil from hard underlying surfaces, i.e., excellent rinsing performance with little surface damage. It can therefore be concluded that the characteristic shape of the abrasive article has a surprisingly significant effect on food soil removal performance.
[0050] Table 4: Food Soil Removal and Coating Weight Based on Abrasive Article Pattern
[0051]
[0052] The "Hexagon", "Dot" and "FPS" patterns are shown in Figure 6 , Figure 7 and Figure 8 As can be seen from Table 4, the pattern with the four-point star (FPS) feature removed about 44% more food soil than the "hexagon" or "dot" pattern, despite a composite coating weight that was about 50% lower. Unlike the features in the "hexagon" and "dot" patterns, the FPS feature is a concave polygon, meaning it has at least one interior angle that measures 180° < 8 < 360°. This geometry creates a sharp, plow-like exposed edge that may contribute to the higher performance.
[0053] In one embodiment, the shaped features of the abrasive article may be substantially flat. Food soil removal results for three-point star (TPS), four-point star (FPS), and six-point star (SPS) abrasive composites made from the composition of Example 2 and having such modified features are shown in Table 5 below. Figures 9 to 11 Exemplary depictions of TPS, FPS, and SPS abrasive composites having pointed and flat top surfaces, respectively, are shown.
[0054] Table 5. Food Soil Removal
[0055]
[0056] As can be seen from Table 5, the flat top surface caused a significant decrease in the flushing performance throughout the test. This indicates that the relatively sharp top surface plays a relatively important role in the flushing performance.
[0057] Effect of Abrasive Minerals on Performance
[0058] An unexpected aspect of the performance of the shaped flushing features of the present invention is that the size and concentration of the abrasive mineral used in the mineral phase or particulate particle phase is relatively unimportant. In the examples below, aluminum oxide was used as the mineral in the abrasive composite formulation for hexagonal flushing features. The results are shown in Table 6, in contrast to the results for the industrial abrasive product, where the effects of abrasive particle size and concentration are easily identified.
[0059] Table 6: Effect of Al2O3 particle size and loading on food soil removal performance of "hexagonal" cone flushing feature
[0060] Example <![CDATA[Al2O3 particle size (grit)]]> wt% abrasive Dirt removal % EX3 1200 20% 47.5% EX4 600 15% 53.4% EX5 600 20% 53.2% EX6 600 40% 58.4% EX7 240 20% 52.8% EX8 <![CDATA[CaCO3 control]]> NA 47.8%
[0061] The lack of an aluminum oxide effect illustrates an important mechanical difference between engineered abrasive features used in household cleaning and those used in industrial applications, and provides valuable insights for designing rinse-off formulations. In industry, abrasives are often used with handheld or stationary power tools that are capable of providing greater pressures and higher speeds than the human arm or a Schieffer machine. When high pressures and speeds are used, the engineered abrasive features break down (through wear and fracture) more quickly, continually exposing new abrasive minerals. However, when abrasives are used by hand or on a Schieffer machine (i.e., at lower pressures and speeds), the abrasive composites generally do not fracture and wear slowly. Therefore, in contrast to abrasives used for industrial purposes, where the abrasive mineral particles are not located on the surface of the product, the abrasive properties of rinse-off products used for household cleaning come from the mechanical properties of the composite as a whole, rather than from individual abrasive particles.
Claims
1. A structured abrasive product, comprising: a substrate having a first major surface and a second major surface; as well as a plurality of shaped abrasive composites, Each of the shaped abrasive composites includes a bottom surface in contact with the first major surface of the substrate, wherein each of the bottom surfaces is in the shape of a concave polygon, and wherein each of the concave polygons has a convex hull with n sides.
2. The structured abrasive article according to claim 1, wherein the value of n is 3.
3. The structured abrasive article of claim 1, wherein the bottom surface has a star-shaped polygonal shape. The structured abrasive article of claim 3 , wherein the bottom surface has a regular star-shaped polygonal shape.
5. The structured abrasive article of claim 1, wherein each of the shaped abrasive composites has a top surface defined as a point, a line, or a plane.
6. The structured abrasive article of claim 1, wherein the shaped abrasive composites can be of different shapes or sizes.
7. The structured abrasive article of claim 1, wherein the shaped abrasive composites are arranged in an ordered pattern.
8. The structured abrasive article of claim 1, wherein the shaped abrasive composites are arranged in a random pattern.
9. The structured abrasive article of claim 1, wherein the longest diagonal of the bottom surface is between 0.3 mm and 6 mm.
10. A structured abrasive article, comprising: a substrate having a first major surface and a second major surface; as well as at least one shaped abrasive composite, the at least one shaped abrasive composite having a bottom surface, wherein the bottom surface of the at least one shaped abrasive composite is positioned on the first major surface of the substrate, And wherein the bottom surface of the shaped abrasive composite has at least one reentrant corner.
11. The structured abrasive article of claim 10, wherein the bottom surface of the shaped abrasive composites has 1 to n vertices, the vertices having reentrant angles.
12. The structured abrasive article of claim 10, wherein the bottom surface has a star-shaped polygonal shape.
13. The structured abrasive article of claim 10, wherein each of the shaped abrasive composites has a top surface defined as a point, a line, or a plane.
14. The structured abrasive article of claim 10 comprising a plurality of shaped abrasive composites.
15. The structured abrasive article of claim 14, wherein the shaped abrasive composites can be of a structured shape or size.
16. The shaped abrasive article of claim 14, wherein the shaped abrasive composites are arranged in an ordered pattern.
17. The article of claim 14, wherein the shaped abrasive composites are arranged in a random pattern.
18. The shaped abrasive of claim 14, wherein the shaped abrasive composites form a non-continuous layer along the first major surface of the substrate.
19. A shaped abrasive composite, the shaped abrasive composite comprising: Binder phase; and a microparticle phase, the microparticle phase being dispersed in the binder phase, Wherein the shaped abrasive composite has at least one reentrant corner.
20. The shaped abrasive composite of claim 19, wherein the shaped abrasive composite has at least three reentrant corners.
Citation Information
Patent Citations
Method of making an abrasive article
US5435816A
Nail tool and method of using same to file, polish and / or buff a fingernail or a toenail
US5658184A
Structured abrasive article adapted to abrade a mild steel workpiece
US5851247A
Method for knurling a workpiece
US5946991A